2021
DOI: 10.1155/2021/7580486
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Type-2 Diabetes Duration and Major Adverse Cardiac Events after Percutaneous Coronary Intervention

Abstract: Background. Diabetes is an independent risk factor for coronary artery disease and portends adverse prognosis in diabetic patients undergoing percutaneous coronary intervention (PCI) compared to nondiabetic patients. Few studies are currently available regarding the relationship between diabetes duration and major adverse cardiac events (MACEs) post-PCI. This study is aimed at assessing the association between diabetes duration and major adverse cardiac events after PCI. Methods. A total of 302 cases of diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Diabetes remained an independent predictor for TLF (HR: 2.712; CI: 1.254–5.864; P =0.011) and TLR (HR: 3.698; CI: 1.112–12.298; P =0.033) after adjustment. Our findings are in keeping with the previous studies that reported acceptable low rates of TLF and MACE with DCB in the small vessel [ 11 , 21 , 29 , 31 37 ]. The PEPCAD I study reported 6.1% MACE events' rates after 12-month follow-up; the BASKET-SMALL 2 trial observed 7.5% MACE rates in the DCB arm [ 23 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Diabetes remained an independent predictor for TLF (HR: 2.712; CI: 1.254–5.864; P =0.011) and TLR (HR: 3.698; CI: 1.112–12.298; P =0.033) after adjustment. Our findings are in keeping with the previous studies that reported acceptable low rates of TLF and MACE with DCB in the small vessel [ 11 , 21 , 29 , 31 37 ]. The PEPCAD I study reported 6.1% MACE events' rates after 12-month follow-up; the BASKET-SMALL 2 trial observed 7.5% MACE rates in the DCB arm [ 23 , 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…Besides, there is an established association between small vessel coronary disease with diabetes mellitus, which is also a powerful predictor for poor outcomes after PCI [1,[14][15][16][17][18][19][20]. Conceived to overcome the drawbacks observed with DES, emerging evidence suggests using drug-coating balloons (DCB) as an interesting alternative treatment strategy in small vessel disease [21][22][23][24][25]. Because of the higher prevalence of SVD observed in diabetic patients, this group of patients is more likely to be treated with the drug-coated balloon.…”
Section: Introductionmentioning
confidence: 99%
“…Such factors included duration of DM, 13 the longer duration of type II DM is not only a significant risk factor for the development of multi-vessel disease, but it has been reported to be a significant independent predictor of 1-year major adverse cardiovascular events rate after percutaneous coronary intervention. 14 Addition to the duration of DM, poor glycemic control is another important clinical determinant found to be strongly associated with a higher risk of MVD, as observed by Pathak SR et al 13 72.2% vs. 10% multi-vessel diseases among patients with poor (HbA1c > 8.5%) and good glycemic control (HbA1c < 7.0%), respectively. Older age is the most commonly reported factor among other clinical predictors of multi-vessel disease.…”
Section: Discussionmentioning
confidence: 92%
“…Chronic complications were noted in only 20.9% of the patients in the present study, most likely due to the facts that diabetes mellitus onset for the majority was <10 years and most patients were aged <60 years. The longer a patient has T2DM, the more vascular complications there are, particularly cardiovascular complications ( 38 ). A study performed in Israel on 5,869 COVID-19 individuals with T2DM revealed that for the majority of patients T2DM onset was >10 years ( 22 ).…”
Section: Discussionmentioning
confidence: 99%